Mortality of Solenopsis invicta Workers (Hymenoptera: Formicidae) After Indirect Exposure to Spores of Three Entomopathogenic Fungi. Issue 3 (13th June 2018) - Rojas, M Guadalupe; Elliott, Robert B; Morales-Ramos, Juan A
Abstract: Mortality caused by indirect exposure to Metarhizium brunneum and Beauveria bassiana (GHA and NI8) to the red imported fire ant, Solenopsis invicta Buren (Hymenoptera: Formicidae), workers was evaluated. Groups of 50 workers were placed in one side of dual-box arenas. The opposite side of the arenas was lined with filter paper squares previously sprayed with unformulated purified spores (10 6 spores/ml) suspended in 0.2% Ethal TDA 3, HLB 8 of the three fungal strains, or untreated filter paper squares as the control. Daily observations were done for 1 wk to determine mortality. Dead ants from each treatment and control were collected, surface cleaned, and placed in PDA media and incubated at 27°C, 60% RH for 7 d to detect fungal growth. The presence of fungal growth in the dead ants confirmed that fungal spores infected workers while walking on the treated paper. In the M. brunneum and B. bassiana GHA treatments, 51.35 and 56.68% of the workers died, respectively, during days 1 and 2. However, only 9.47 and 35.96% of the mortality could be explained by fungal infection by M. brunneum and B. bassiana GHA, respectively. Most of the mortality observed in the B. bassiana NI8 treatment (84.48%) occurred later (between days 4–6) and most of this mortality occurring during day 4 (89.06%) could be explained by B. bassiana infection. Overall mortality was significantly higher in the B. bassiana NI8 treatment than the other two fungi tested and control. Potential application of these fungal strains for fire ant control are discussed.